Anxiety, attention, and mindfulness following focused attention and open-monitoring mindfulness meditation - Hanson, Matthew D (My University, 2017)
Research on the effects of mindfulness meditation has been growing exponentially over the past three decades. The purpose of this present study is to explore whether different types of mindfulness meditative techniques differentially affect anxiety, attention, and mindfulness. Specifically, a meditative technique that aims to focus attention on one object, and one that aims to increase attentional flexibility, may affect anxiety, attention, and mindfulness in distinct ways. Participants were randomly assigned to one of three conditions: 1) focused-attention mindfulness meditation, 2) openmonitoring mindfulness meditation, or 3) control condition in which they learned about sensations and perceptions. Anxiety, attention, and mindfulness were measured prior to and after each mindfulness practice or listening control task. The data did not support the beneficial effects of mindfulness meditation on state anxiety or state mindfulness previously found in the literature. Additionally, there was no evidence for differential effects of focused attention compared to open-monitoring mindfulness meditation on anxiety, attention, or mindfulness skills. Limitations to the current study are considered.
A Thesis Submitted In Partial Fulfillment of the Requirements For the Degree of Master of Science-Psychology Cognitive and Affective Science
Keywords: Mindfulness-based cognitive therapy; Meditation; Stress management; Interpersonal relations; Mental discipline; Attention